Using electronic medical records to determine prevalence and treatment of mental disorders in primary care: a database study. (10th April 2015) - Gleeson, M.; Hannigan, A.; Jamali, R.; Su Lin, K.; Klimas, J.; Mannix, M.; Nathan, Y.; O'Connor, R.; O'Gorman, C.; Dunne, C.; Meagher, D.; Cullen, W.
Abstract : Objectives: With prevention and treatment of mental disorders a challenge for primary care and increasing capability of electronic medical records (EMRs) to facilitate research in practice, we aim to determine the prevalence and treatment of mental disorders by using routinely collected clinical data contained in EMRs. Methods: We reviewed EMRs of patients randomly sampled from seven general practices, by piloting a study instrument and extracting data on mental disorders and their treatment. Results: Data were collected on 690 patients (age range 18–95, 52% male, 52% GMS-eligible). A mental disorder (most commonly anxiety/stress, depression and problem alcohol use) was recorded in the clinical records of 139 (20%) during the 2-year study period. While most patients with the common disorders had been prescribed medication (i.e. antidepressants or benzodiazepines), a minority had been referred to other agencies or received psychological interventions. 'Free text' consultation notes and 'prescriptions' were how most patients with disorders were identified. Diagnostic coding alone would have failed to identify 92% of patients with a disorder. Conclusions: Although mental disorders are common in general practice, this study suggests their formal diagnosis, disease coding and access to psychological treatments are priorities for future research efforts.